Internet marketing and its impact on customer loyalty in a car wash company, SJL, 2022 - Ojeda-Vásquez, Angel Omar (LACCEI, 2023)
The objective of this research was to determine the incidence of internet marketing with customer loyalty (and its dimensions: information, internal marketing, communication, customer experience and incentives and privileges) in a car wash company, SJL, 2022. The methodology had a quantitative approach, applied type, explanatory and descriptive level, non-experimental and cross-sectional design. The population consisted of the company’s customers (infinite). The study sample consisted of 68 of the company’s customers. The technique applied was the survey. The instrument was a questionnaire and consisted of 18 items. It was concluded that internet marketing has a significant impact on customer loyalty in a car wash company, SJL, 2022 (sig.=0.000; r2=0. 5929) as well as in its dimension’s information, internal marketing, communication, customer experience and incentives and privileges (sig.=0.000, r2=0.3102; sig.=0.000, r2=0.2304; sig.=0.000, r2=0.3271; sig.=0.000, r2=0.3158; sig.=0.000, r2=0.4872) respectively. Finally, a discussion with background and final conclusions was issued.